Proceedings of the 11th International Conference on Mobile and Ubiquitous Multimedia 2012
DOI: 10.1145/2406367.2406379
|View full text |Cite
|
Sign up to set email alerts
|

Saving energy at work

Abstract: Decreasing the energy consumption is an important goal for individuals and public or industrial institutions. Pervasive games have been used to teach people to save energy in private households. We present Climate Race, a pervasive game addressing office workers. In the user-centered design process, three main requirements were identified: unobtrusiveness, cooperative gameplay and privacy. The implemented prototype monitors energy consumption and relates it to the activities of the player by measuring correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…A number of other interventions in office environments take the form of games. Climate Race [42] used sensors to track players' energy-related behaviour (e.g., switching off lights when not in) awarding positive or negative points as appropriate. In the Energy Chickens game [30], virtual pets represent the energy consumed by individual devices; their visual aspect is designed to encourage staff towards lower consumption.…”
Section: Related Workmentioning
confidence: 99%
“…A number of other interventions in office environments take the form of games. Climate Race [42] used sensors to track players' energy-related behaviour (e.g., switching off lights when not in) awarding positive or negative points as appropriate. In the Energy Chickens game [30], virtual pets represent the energy consumed by individual devices; their visual aspect is designed to encourage staff towards lower consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Specifically, commercial and public buildings offer more challenges in aligning energy consumption per predicted design, mainly due to the lack of occupant motivation and individual accountability (Papaioannou et al, 2017). Specific research on gamification techniques employed to conserve energy in office buildings (Simon et al, 2012;García et al, 2017) have demonstrated the effectiveness of the game-based approach. In fact, the American Council for an Energy Efficient Economy (ACEEE), through its research on more than 50 gamification programs and over 20 case studies meant to influence behavior around energy-efficiency reported three to six percent energy savings in large participant settings and well over 10 percent savings in narrow targeted gamified sustainability programs (Grossberg et al, 2015).…”
Section: Background and Literature Analysismentioning
confidence: 99%
“…The methodologies used to evaluate game-based intervention in the home energy space are diverse, with limited large-scale empirical data available; studies typically seek to provide design-level input through mixed-method or grounded theory approaches (Derek Foster, Lawson, Wardman, Blythe, & Linehan, 2012). Primary design-level evidence suggested by the literature base includes a likely limited impact of points, badges and leaderboards when introduced without an understanding of social context and how participants construct value around rewards (Wiersma, 1992); providing asynchronous feedback, avoiding 'push' notifications (Simon J., Jahn M., & Al-Akkad, 2012); and that challenge may be a stronger motivator than real or virtual incentives (Kalz, Börner, Ternier, & Specht, 2015). In an evaluation of a workplace game for energy consumption, implementing a leaderboard (Tolias E., Costanza E., Rogers A., Bedwell B., & N., 2015), users were observed to cheat, artificially altering their consumption data.…”
Section: Literature Reviewmentioning
confidence: 99%